Harnessing Next-Generation Sequence Technology to Elucidate Healthcare-Associated Infection Transmission Pathways. (October 2020) - Gable, Paige; McAllister, Gillian; Sula, Erisa; Rankin, Danielle A.; Breaker, Erin; Daniels, Jonathan; Chan, Monica Y.; Dotson, Nychie; Walters, Maroya; Halpin, Alison Laufer
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) are multidrug-resistant bacteria that persist in healthcare environments, particularly in wastewater reservoirs where they can pose risks for patients. Healthcare-associated outbreaks of carbapenemase-producing (CP) CRE can be propagated via a single bacterial strain and/or mobile genetic element (MGEs) harboring a carbapenemase gene. Unlike chromosomally encoded carbapenemases, CP-MGEs can rapidly facilitate the spread of these carbapenemase genes across bacterial strains. From July 2017 to December 2018, the Florida Department of Health in Orange County investigated an outbreak of patients colonized with various bacterial genera of CP-CRE carrying the Klebsiella pneumoniae carbapenemase gene ( bla KPC), indicating a potential MGE reservoir. WGS was performed to identify transmission pathways and linked cases, beyond what traditional testing provides. Methods: We selected a subset of bla KPC-harboring isolates for WGS on short- and long-read platforms (MiSeq, PacBio, MinION) to achieve high quality, complete genome and plasmid assemblies. Laboratory, clinical, and epidemiological data were combined to identify possible transmission events, common sources, and common MGEs. Results: Eleven clinical isolates from 5 genera ( Citrobacter, Enterobacter, Klebsiella, Morganella, Providencia, and Serratia ), and 10 environmental isolates collected from the pharmacy and medication room, ICU, and patient rooms and comprising 4 genera ( Citrobacter, Enterobacter, Klebsiella, and Serratia ) underwent WGS. Although short-read WGS elucidated additional subsets of closely related strains, high genomic diversity was also observed within some species: Citrobacter freundii : 13, 483 single-nucleotide variants (SNVs), 67% core genome; Enterobacter spp: 3–18, 563 SNVs; 34%; and K. pneumoniae : 8–18, 460 SNVs, 80%. Further analysis using long-read hybrid assemblies revealed 2 unique bla KPC-harboring plasmids. The first plasmid, pDHQP20145-KPC3 (50 kb), contained the bla KPC-3 gene and was detected in both patient and environmental isolates across 3 of the 5 sequenced genera. The second plasmid, pDHQP201745-KPC2 (180 kb), contained the bla KPC-2 gene, and was found across 2 CP-CRE genera isolated from both patients and the environment, including isolates from the medication room sink drain and a patient who received compounded oral medications. Conclusion: WGS identified 2 bla KPC-harboring plasmids, including pDHQP20145-KPC3, which was found across 3 genera of CP-CRE isolated from patients and the environment, supporting prolonged transmission of KPC-producing CRE in this facility, and a CP-MGE driving transmission. The rapid spread of emerging, potentially mobile, antimicrobial resistance has increased our need to further explore the genomic environment of promiscuous MGEs. WGS can contribute to infection control beyond traditional subtyping methods, such as pulsed-field gel electrophoresis (PFGE), as MGEs increasingly represent an important driver of transmission. Funding: None Disclosures: None